Trust, Hope, and Fortitude as Theological Virtues in Joseph Albo’s Sefer ha-Ikkarim - Green, Alexander (Jewish Thought, 2023)
Joseph Albo’s Sefer ha-Ikkarim was one of the most popular Jewish works of the later Middle Ages. This article shows how in this work, Albo uniquely adopts, develops, and theologizes the ethical categories of Aristotle’s Nicomachean Ethics, such as happiness, friendship, and the virtues, in order to strengthen the commitment of his Jewish followers who were being induced to convert to Christianity. His objective was to convince the Jews that they must remain loyal to their faith, notwithstanding the worldly benefits that they might accrue by becoming Christians. Albo proceeds by arguing that the relationship between God and Israel represents the highest form of loving relationship based on utility, pleasure, and goodness, but that it is ultimately one that is reasonless from God’s perspective. Hence, it is an enduring relationship that cannot be undone, as avowed in the biblical covenant between God and Israel, promising eternal happiness that transcends the limited worldly happiness of human flourishing. While the moral virtues are necessary for human flourishing and are perfected and applied to particulars by the Torah in a manner that cannot be achieved by the human intellect alone, the sustainability of the covenant requires a supplementary set of theological virtues. For Albo, the theological virtues of trust, hope, and fortitude are necessary for the maintenance of the covenant and the Torah, especially during times of adversity. All three traits bolster the Jewish people’s ability to withstand societal and religious pressures to abandon Judaism in times of duress.